Fotogrametría en el diseño y construcción de obras de ingeniería civil - Cabrera Ruíz, Bulmaro (My University, 1979)
Highway engineering has constantly to be developed to meet new or extended requirements on: environment, traffic safety, community planning, traffic coat
Keywords: photogrammetry; evaluation; data; processing; architecture; applications